Biofunctional nanomaterials based on ultra fine silica, protein and aminocarbohydrates - Galagan, N.P.; Klymenko, N.Y.; Orel, I.L.; Novikova, E.A.; Turov, V.V. (Вiopolymers and Cell, 2010)
Aim. Investigation of adsorptive interactions of N-acetyl-D-glucosamine (GlcNAc) and N-acetylneuraminic acid (NANA) with ultra fine silica (UFS) modified by protein bovine serum albumin (BSA). Methods. Adsorption, IR-, 1H NMR- and laser Doppler spectroscopy. Results. Conditions for obtaining bionanocomposites (BNC) UFS/GlcNAc, UFS/BSA/GlcNAc and UFS/BSA/NANA are developed. Conclusions. Impellent ability of deconservated bovine gametes decreased in the presence of BNC after adsorptive fastening of protein on UFS surface. The 1H NMR spectroscopy data proved that interaction of GlcNAc with protein was accompanied by essential dehydratation of protein molecules. Цель. Исследование адсорбционных взаимодействий N-ацетил-D-глюкозамина (GlcNAc) и N-ацетилнейраминовой кислоты (N-АНК) с высокодисперсным кремнеземом (ВДК), модифицированным белком бычьим сывороточным альбумином (БСА). Методы. Адсорбция, ИК-, 1Н ЯМР- и лазерно-допплеровская спектроскопия. Результаты. Разработаны условия получения бионанокомпозитов (БНК) ВДК/GlcNAc; ВДК/БСА/GlcNAc и ВДК/БСА/N-АНК. Выводы. Двигательная способность деконсервированных гамет быка снижается в присутствии БНК после адсорбционного закрепления на его поверхности белка. На основе данных 1Н ЯМР-спектроскопии установлено, что взаимодействие GlcNAc с белком сопровождается сильной дегидратацией его молекул. Мета. Дослідження адсорбційних взаємодій N-ацетил-D-глюкозаміну (GlcNAc) та N-ацетилнейрамінової кислоти (N-АНК) з високодисперсним кремнеземом (ВДК), модифікованим білком бичачим сироватковим альбуміном (БСА). Методи. Адсорбція, ІЧ-, 1Н ЯМР- та лазерно-допплерівська спектроскопія. Результати. Розроблено умови отримання біонанокомпозитів (БНК): ВДК/GlcNAc; ВДК/БСА/GlcNAc та ВДК/БСА/N- АНК. Висновки. Здатність до руху деконсервованих гамет бика знижується за присутності БНК після адсорбційного закріплення на його поверхні білка. На основі даних 1Н ЯМР- спектроскопії встановлено, що взаємодія GlcNAc з білком супроводжується сильною дегідратацією його молекул.